Analisis Karakter Aparatur Sipil Negara (ASN) Ditinjau dari Komunikasi Interpersonal - Dewi, Agil Rimba Candra Ayu; Nihayati, Badi' Zulfa (Nusantara Innovation Journal, 2024)
The level of performance of PPPK teachers as one of the ASN in the education sector shows the quality of education in Indonesia. One aspect that can help improve teacher performance is having adequate character. Minister of Manpower Regulation Number 3 of 2023 concerning ASN work culture and code of ethics states that the basic values ​​of AKHLAK are the basis for strengthening work culture and supporting the improvement of ASN performance. Having adequate character as a teacher can help carry out teacher duties in accordance with the values ​​of AKHLAK in creating an adequate work culture and level of performance. This research analyze the characteristics of Generation Z SMA/SMK PPPK teachers in East Kalimantan using an interpersonal communication perspective. DeVito’s theory of interpersonal communication and interpersonal power is used in this research with the aim of finding out what the character is and whether there is a possibility of abuse of power and bullying occurring among generation Z high school/vocational school PPPK teachers in East Kalimantan when viewed from interpersonal communication. Descriptive quantitative methods are used to explain simple quantitative data descriptively. The results found in this research are that generation Z SMA/SMK PPPK teachers in East Kalimantan have characters which include charismatic, competitive, expert in their field, consistent, have a good self-image, trustworthy and honest; Apart from that, there is the possibility of abuse of power (domination by one party and a sense of excessive interference); and bullying in the educational environment in East Kalimantan.